Pharmacological cognitive enhancement: a promising or an inevitable future? - Oliveira, Rafael Cardoso (2021)
Human cognitive functions are often targets of curiosity, study and reflections, since they are essential for human beings. Understanding our cognitive boundaries, the processes that originate them,and how to overcome them means comprehending the human condition and the consequences of manipulating cognition. In recent years, growing interest has been observed in cognitive enhancement with the help of drugs, resulting in several important ethical, medical, and legal dilemmas. This article analyzed the ethical issues involved in this process and concluded that pharmacological cognitive enhancement needs further studies at the pharmacodynamic level, so that its application – regulatedand in specific contexts – can benefit individuals and society, without undermining the authenticity of the human condition.